Complex assessment model for advanced technology deployment - Kildienė, Simona; Zavadskas, Edmundas Kazimieras; Tamošaitienė, Jolanta (Journal of Civil Engineering and Management, 2014)
The construction sector constantly offers new products, more effective technologies and novel solutions aimed at improvement of the quality of human habitats and wider distribution of technologies. Currently, effective technologies that require less time and costs for production, installation and use are gaining greater significance. Among them are construction materials and technologies with increasingly popular sustainability features. Considering the above, the article offers a complex algorithm for assessing the deployment and distribution potential of a new technology/product. For this purpose, a multi-stage model of alternatives and criteria was suggested and an analytical multi-stage evaluation model has been designed. The practical example illustrates the assessment of micro environment using a combination of AHP (Analytic Hierarchy Process) and Permutation methods. The designed multi-criteria assessment model promotes accessibility of users to a technology, new product, a part of the product and a technological process.